Broadcast of Things - A Thought Experiment - Hartmann, Markus; Tröger, Hans-Martin; Kilian, Gerd; Robert, Jörg; Nowak, Thorsten; Heuberger, Albert (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2014)
Sensor networks as well as the Internet of Things, are getting more and more popular in many numbers of applications. However, a bidirectional link between the individual nodes is not always needed and leads to higher costs and power consumption. This paper introduces the concept Broadcast of Things which reverses the well known broadcast architecture. It is shown that in realistic environments the proposed concept of broadcasting sensor nodes offers an interesting alternative to usual sensor networks. By simulations the efficiency benefits of broadcasting sensor nodes is illustrated. To give an idea about the capability of the broadcast concept, a 1 cm3 cubic demonstrator is shown. With a discussion and summary about the different efficiencies by the two concepts this paper is concluded. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.komele.broadc
Keywords: Broadcast of Things; efficiency; propagation model; sphere packing bound; wireless sensor networks